Evolution of anthropometric and physical performance characteristics of international male cricketers from 2014 to 2020 in a World Cup winning nation - Scott, P.; Ahmun, R.; de Weymarn, C.; Gardner, E.; Bliss, A.; Jones, T. W.; Callaghan, S. J.; Tallent, J. (International Journal of Sports Science & Coaching, 2023)
The aim of the study was to firstly present a comprehensive physical profile of international cricketers in a World Cup winning cricket nation. Secondly, to describe changes in physical profiles across seven years. Fifty-two senior international cricketers` physical profiles were retrospectively analysed across seven years. Using linear mixed-modelling, changes in stature, body mass, sum-of-8 skinfolds, sprinting time (10 and 40 m), run-2 time, counter movement jump (CMJ), push and pull strength capacity and the Yo-Yo intermittent recovery test level-1 (Yo-Yo-IR1) were analysed during a seven-year period. There were no significant changes in body mass (p = .63) or stature (p = .99) during this time. However, there was a significant (p < .001) mean decrease of ~14 mm in the sum-of-8 skinfolds. Distance covered in the Yo-Yo-IR1 also showed a significant (p = .002) effect of years, with a mean increase of 459 m in 2017 when compared with 2014. A significantly (p = .01) more balanced push-to-pull strength capacity ratio was also evident across years as a result of a significant (p < .001) increase in pull strength capacity. Significant (p < .05) fluctuations in CMJ, sprint and run-2 time were seen, with no obvious trends. International cricketers within our study have gone through a notable physical transformation that has likely resulted in an increase in lean mass and aerobic capacity. The change across time to a more balanced push-to-pull strength capacity may be beneficial for injury prevention.